The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1016/j.tet.2017.04.038
|View full text |Cite
|
Sign up to set email alerts
|

Expansion of the assembly of cowpea chlorotic mottle virus towards non-native and physiological conditions

Abstract: a b s t r a c tThe cowpea chlorotic mottle virus (CCMV) is a nanoparticle that holds promise for diagnostic and therapeutic applications. The empty virus-like particle, however, is not stable under physiological conditions. Here, we describe a systematic study into the expansion of the assembly properties of a proteinbased block copolymer of the CCMV capsid protein and an elastin-like polypeptide. By systematically changing the hydrophobicity of the stimulus-responsive elastin-like polypeptide block, assembly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 11 publications
0
24
0
Order By: Relevance
“…Interestingly, this native ELP‐CCMV showed surprisingly high stability up to 50 °C in pH 5.0 buffer ( T= 3 particles by pH‐induced assembly); however, over an extended incubation period under these conditions, a large fraction of the protein aggregated. In pH 7.5 buffer containing 2.5 m NaCl ( T= 1 particles by ELP‐induced assembly), the protein also demonstrated high stability; however, at more physiologically relevant salt concentrations (500 m m NaCl), capsid assembly did not occur, as we reported previously; this indicated the need for more hydrophobic variants …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Interestingly, this native ELP‐CCMV showed surprisingly high stability up to 50 °C in pH 5.0 buffer ( T= 3 particles by pH‐induced assembly); however, over an extended incubation period under these conditions, a large fraction of the protein aggregated. In pH 7.5 buffer containing 2.5 m NaCl ( T= 1 particles by ELP‐induced assembly), the protein also demonstrated high stability; however, at more physiologically relevant salt concentrations (500 m m NaCl), capsid assembly did not occur, as we reported previously; this indicated the need for more hydrophobic variants …”
Section: Resultsmentioning
confidence: 99%
“…In pH 7.5 buffer containing 2.5 m NaCl (T = 1p articles by ELP-induceda ssembly), the protein also demonstrated high stability; however,a tm ore physiologically relevant salt concentrations( 500 mm NaCl), capsid assembly did not occur,a sw er eportedp reviously;t his indicated the need for more hydrophobic variants. [36] Next, the assembly behavioro fb oth hydrophobic variants was determined (see Figure S7 in the Supporting Information). DLS experiments showed that the capsids of these variants remained assembled in pH 5.0 buffer.I nterestingly,i np H7.5 buffer containing 500 mm NaCl, the capsids did not completely disassemble;t his indicatest he higher stability of these hydrophobic variants relative to that of the native ELP-CCMV.B ecause ELP-CCMV assembly behavior and stability are dependent on many variables, namely,s alt, capsid protein concentration, pH, temperature, and time, [35] am ore extensive dialysis was performed overnight at 4 8Ct oa chievef ull disassembly of these more hydrophobic variants.…”
Section: Assemblyb Ehavior Of the Elp-ccmv Variantsmentioning
confidence: 99%
See 3 more Smart Citations